MYORG Mutation Heterozygosity Is Associated With Brain Calcification. Issue 4 (17th January 2020) - Chen, You; Cen, Zhidong; Chen, Xinhui; Wang, Haotian; Chen, Si; Yang, Dehao; Fu, Feng; Wang, Lebo; Liu, Peng; Wu, Hongwei; Zheng, Xiaosheng; Xie, Fei; et al.
Abstract: Background: Biallelic mutations in the MYORG gene were first identified as the cause of recessively inherited primary familial brain calcification. Interestingly, some heterozygous carriers also exhibited brain calcifications. Objectives: To further investigate the role of single heterozygous MYORG mutations in the development of brain calcifications. Methods: A nation‐wide cohort of Chinese primary familial brain calcification probands was enrolled from March 2016 through September 2019. Mutational analysis of MYORG was performed in 435 primary familial brain calcification probands who were negative for mutations in the other four known primary familial brain calcification–causative genes ( SLC20A2, PDGFRB, PDGFB, and XPR1 ). Results: Biallelic MYORG mutations were identified in 14 primary familial brain calcification patients from 10 unrelated families. Interestingly, 12 heterozygous carriers from seven of these families also exhibited mild‐to‐moderate brain calcifications. Moreover, single heterozygous mutations were detected in an additional 9 probands and in 7 of their family members affected with brain calcifications. In our cohort, clinical and imaging penetrance of individuals with biallelic mutations were 100%, whereas among individuals with heterozygous mutations, penetrance of imaging phenotype was reduced to 73.7% (28 of 38) and clinical penetrance was much lower. Most (34 of 38) remained asymptomatic whereas 4 carriers had symptoms of uncertain clinical significance (nonspecific depression, epilepsy and late‐onset parkinsonism). Compared with individuals with biallelic MYORG mutations, individuals with heterozygous mutations had brain calcifications with much lower calcification scores ( P < 2e‐16). Conclusions: Presence of brain calcifications in individuals with heterozygous MYORG mutations suggested a semidominant inheritance pattern with incomplete penetrance. This finding further expanded the genotype‐phenotype correlations of MYORG ‐related primary familial brain calcification. © 2020 International Parkinson and Movement Disorder Society